KESANTUNAN BERBAHASA PADA PEMBELAJARAN MAHASISWA UNIVERSITAS PUTERA BATAM - afriana afriana; Robby Satria Mandala (BASIS (Bahasa dan Sastra Inggris), 2018)
The purpose of this study was to describe the attitude of the language towards the politeness of the language of the students of Putera Batam University. This study used a survey method. The sample in this study were 43 students of English Literature. Data obtained from observation sheets and questionnaires. Assessment is done using a Likert scale. The data analysis technique used descriptive statistics using technical regression analysis. The results of the study showed that language attitudes had a positive effect on student politeness. This finding recommends that the development of language attitudes will improve student language politeness. This study aims to analyze the language attitude of students of the English Literature study program at Putera University, then analyze the politeness of the students of the English Literature Study Program at the Putera Batam University. And the influence of language attitudes on the politeness of the language of students of English Literature Study Program, Putera Batam University.